PEMANFAATAN SISA MEDIA JAMUR PELAPUK PADA DEKOMPOSISI LIMBAH PADAT PULP Acacia mangium - Sihati Suprapti; Djarwanto; Sri Komarayati (BRIN Publishing, 2017)
Currently, Ganoderma lucidum, Pleurotus ostreatus, and P. sajor-caju are prospective fungi for decomposition of pulp and paper industry’s waste. This paper studies the possible utilization of rotting fungi spent compost for decomposition of mangium sludge. Initially, the fungi were cultivated for three months on medium prepared from sengon (Falcataria moluccana) wood sawdust. The rotting fungi spent compost was then used for degrader activator by inoculating them into the Acacia mangium sludge, then, incubated for six months. Results revealed that after three month incubation the values of the Biological Conversion Efficiency (BCE) of sengon reached 13.41% (G. lucidum), 47.11% (P. ostreatus), and 38.06% (P. sajor-caju). Fungal inoculation into the sludge improved the C/N ratio as much as 71.59%. The usage of higher concentration of G. lucidum inoculums increased the C/N ratio value. After six months incubation, some sludge contents reduced by 48.76% (N), 35.42% (P) and 25% (K), except for Ca and Mg, which increased by 112.9% and 6.67%, respectively. Mineral content of the untreated sludge decreased by about 66.12% (Ca), 68.75% (P) and 4.17% (Mg), except for K and Ca which were increased by 2.08% and 64.52%, respectively. Cation exchange capacity (CEC) value of the sludge after incubation increased by about 3.85% (control) and 56.8% (treated).